Analysis of slag and fuel samples from Smoo Cave (Scottish Historical and Archaeological Internet Reports, 2005)
The concentration of iron in one of the three samples is suggestive of iron smithing slag. However, work on traditional bloomery making in the Highlands has revealed a relatively high percentage of iron in what is certainly tap slag from a smelting cycle.